ASSESSMENT OF MICRO-SHEAR BOND STRENGTH OF BIODENTINE TO VARIOUS RESTORATIVE MATERIALS AFTER AGING: AN IN - VITRO STUDY - Dr. Sonia Meshram, Dr. Rahul Ramteke, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: This study aimed to determine the perfect timing for restoratives installations of the micro-shear bond strength (µSBS) of Biodentine with various restorative materials. Materials and Methods: Sixty Biodentine specimens were prepared and categorized into two groups based on aging periods: one week and two weeks. Each group was further divided into three subgroups according to the restorative material used—Short Fiber-Reinforced Composite, Zirconomer, and Cention N—with ten specimens in each subgroup.